Efficacy, pharmacokinetics and neurocognitive performance of dual, NRTI-sparing antiretroviral therapy in acute HIV-infection. (1st November 2020) - Gay, Cynthia L.; Neo, Dayna T.; Devanathan, Aaron S.; Kuruc, Joann D.; McGee, Kara S.; Schmitz, John L.; Sebastian, Joe; Shaheen, Nicholas J.; Ferrari, Guido; McKellar, Mehri; Fiscus, Susan A.; Hicks, Charles B.; et al.
Abstract : Objectives: The aim of this study was to evaluate penetration of antiretrovirals into compartments and efficacy of a dual, NRTI-sparing regimen in acute HIV infection (AHI). Design: Single-arm, open-label pilot study of participants with AHI initiating ritonavir-boosted darunavir 800 mg once daily and etravirine 400 mg once daily or 200 mg twice daily within 30 days of AHI diagnosis. Methods: Efficacy was defined as HIV RNA less than 200 copies/ml by week 24. Optional sub-studies included pharmacokinetics analysis from genital fluids (weeks 0–4, 12, 48), cerebrospinal fluid (CSF) (weeks 2–4, 24 and 48) and endoscopic biopsies (weeks 4–12 and 36–48). Neuropsychological performance was assessed at weeks 0, 24 and 48. Results: Fifteen AHI participants were enrolled. Twelve (80%) participants achieved HIV RNA less than 200 copies/ml by week 24. Among 12 participants retained through week 48, nine (75%) remained suppressed to less than 50 copies/ml. The median time from ART initiation to suppression less than 200 and less than 50 copies/ml was 59 and 86 days, respectively. The penetration ratios for etravirine and darunavir in gut associated lymphoid tissue were 19.2 and 3.05, respectively. Most AHI participants achieving viral suppression experienced neurocognitive improvement. Of the three participants without overall improvement in neurocognitive functioning as measured by impairment ratings (more than two tests below 1 SD), two had virologic failure. Conclusion: NRTI-sparing ART started during AHI resulted in rapid viral suppression similar to NRTI-based regimens. More novel and compact two-drug treatments for AHI should be considered. Early institution of ART during AHI appears to improve overall neurocognitive function and may reduce the risk of subsequent neurocognitive impairment. ClinicalTrials.gov: NCT00855413 Abstract : Supplemental Digital Content is available in the text